Becoming an engaged educational leader : navigating mid-career growth and development - Marshall, Ian A.; Jackman, Grace-Anne (Navigating the leadership continuum: connecting theory, research and practitioners' perspectives, 2024)
"Explore the uncharted territory of mid-career educational leadership with "Becoming an Engaged Educational Leader: Navigating Mid-Career Growth and Development." This book addresses the notable gap in educational leadership literature, focusing on the pivotal but often overlooked mid-career phase. It doesn't aim to be the ultimate guide but serves as a catalyst to stimulate critical thinking, dialogue, and action among educational leaders. Mid-career leadership is a phase where experienced leaders grapple with unique challenges, standing at the crossroads of their careers. This book delves into the multifaceted aspects of mid-career educational leadership, offering readers a comparative lens by drawing upon experiences and practices from different countries. It recognizes that educational systems are influenced by cultural, social, and economic factors specific to each jurisdiction. Intended for mid-career educational leaders and administrators, as well as educators shaping the next generation of leaders, this resource provides valuable insights and practical guidance. With vignettes and reflective questions at the end of each chapter, it fosters critical thinking and meaningful discussions among students. Join us on a journey to enhance mid-career leadership in education and contribute to the overall improvement of our educational systems"--